Studies on the systematics and taxonomy of the genus Hylaeus F. (10) New descriptions and records of Asian Hylaeus species (Hymenoptera: Anthophila, Colletidae). - Dathe, Holger H. (Contributions to Entomology = Beiträge zur Entomologie, 2015)
One new species from the Sinai Peninsula, Hylaeus (Hylaeus) oliviae spec. nov., and four new species from China are described: Hylaeus (Hylaeus) ascheri spec. nov., Hylaeus (Hylaeus) maoxianus spec. nov., Hylaeus (Hylaeus) rozenius spec. nov. and Hylaeus (Paraprosopis) lushanicus spec. nov. New data are presented on the distribution of further species, Hylaeus (Hylaeus) bimaculatus Chen & Xu, Hylaeus (Hylaeus) sibiricus (Strand), Hylaeus (Hylaeus) tsingtauensis (Strand), Hylaeus (Nesoprosopis) floralis (Smith), Hylaeus (Nesoprosopis) transversalis Cockerell, Hylaeus (Patagiata) nigrocuneatus Cockerell and Hylaeus (Prosopis) ikudomei Chen & Xu. Hylaeus (Nesoprosopis) dathei Chen & Xu is recognised as a new synonym of Hylaeus (Nesoprosopis) transversalis Cockerell. Keywords China, Sinai, bee taxonomy, new species, synonymy, distribution. Nomenclatural Acts ascheri Dathe, 2015 (Hylaeus (Hylaeus)), spec. n. maoxianus Dathe, 2015 (Hylaeus (Hylaeus)), spec. n. oliviae Dathe, 2015 (Hylaeus (Hylaeus)), spec. n. rozenius Dathe, 2015 (Hylaeus (Hylaeus)), spec. n. dathei Chen & Xu, 2012 (Hylaeus (Nesoprosopis)), syn. n. pro Hylaeus (Neoprosopis) transversalis Cockerell, 1924 lushanicus Dathe, 2015 (Hylaeus (Paraprosopis)), spec. n.